2011
DOI: 10.1111/j.1748-720x.2011.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

The Return of Results of Deceased Research Participants

Abstract: The death of a research participant raises numerous ethical and legal issues regarding the return of research results to related family members. This question is particularly acute in the context of genetic research since the research results from an individual may be relevant to each of the biological relatives. This paper first investigates the ethical and legal frameworks governing the return of a deceased participant's individual research results to his or her related family members. Then, it weighs the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…1 Despite this lack of clarity, the discussion has moved to the offer of research results to family members of participants, including when the participant is deceased. 2 Given the familial implications of genetic information, this extension is perhaps logical. But it raises concerns throughout the research process, including, for example, questions about disclosures and choices on consent forms, procedures for identifying and contacting family members, and how any such obligations might apply to secondary users of biospecimens and data.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite this lack of clarity, the discussion has moved to the offer of research results to family members of participants, including when the participant is deceased. 2 Given the familial implications of genetic information, this extension is perhaps logical. But it raises concerns throughout the research process, including, for example, questions about disclosures and choices on consent forms, procedures for identifying and contacting family members, and how any such obligations might apply to secondary users of biospecimens and data.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitive nature of genetic information, the time elapsed since death, the expressed wishes of the deceased to disclose the results (or not), the family members' wishes to receive them (or not), and the relevance of the results for the health of living relatives must all be considered (Tassé 2011;Bredenoord 2012;Chan et al 2012;Boers 2015).…”
Section: Family Members Of Deceased Individualsmentioning
confidence: 99%
“…Regarding the disclosure of research results, a consensus seems to emerge from the literature (Tassé 2011;Bredenoord 2012;Boers 2015) and guidelines, that genetic research results from a deceased participant could be returned to family members if (RMGA 2016) 1) they meet generally accepted criteria of scientific and clinical validity; 2) they have significant implications for family members; 3) the participant has previously consented that they be transmitted to family members; 4) REB approval has been obtained; 5) the family (i.e., the persons directly affected by the results) have consented; and 6) the research result has been confirmed.…”
Section: Family Members Of Deceased Individualsmentioning
confidence: 99%
“…One may consider genetic information belonging to the family, especially after the death of a patient, however the laws surrounding privacy change over time and are by no means consistent across different jurisdictions 32 . There is a fine balance between respecting the privacy and wishes of the deceased versus the health interests and needs of the family.…”
Section: Family Implicationsmentioning
confidence: 99%